Honey bee envenoming in Santa Catarina, Brazil, 2007 through 2017: an observational, retrospective cohort study - Oliveira, Suzana Kniphoff de; Trevisol, Daisson Jose; Parma, Gabriel Cremona; Ferreira Jonior, Rui Seabra [UNESP]; Barbosa, Alexandre Naime [UNESP]; Barraviera, Benedito [UNESP]; Schuelter-Trevisol, Fabiana (Soc Brasileira Medicina Tropical, 2019)
Introduction: We evaluated the epidemiological and clinical profile of reported cases of bee sting incidents in Santa Catarina, Brazil. Methods: This retrospective cohort study included all reported cases of bee sting incidents among the population of Santa Catarina from 2007 to 2017. Results: In total, 8,912 cases were reported, corresponding to an overall rate of 12.3/100,000 population. The mean age was 29,8 years with 60.2% men. The lethality rate was 0.2%. Conclusions: Santa Catarina has a high incidence rate of bee stings, which is higher than the national average. The data presented in this study may be underestimated.
Keywords: Africanized honeybee; Santa Catarina; Brazil; Envenoming